Prevalence of Zoonotic Parasites in Drinking Water and Sanitation Practices in Rural Areas of Dera Ismail Khan, Khyber Pakhtunkhwa, Pakistan - Muhammad, Khalid; Muhammad, Tooba; Murtaza, Ghulam; Khan, Inam Ullah; Malik, M. Inam Ullah; Shah, Ayesha Haleem; Shah, Jawad Ullah; Zaman, Ali (Journal of Agriculture and Veterinary Science, 2026)
ABSTRACTAccess to safe drinking water remains a critical public health challenge in rural regions, where water scarcity, inadequate sanitation, and dependence on multiple water sources increase the risk of waterborne and zoonotic parasitic infections. Tehsil Daraban Kalan, District Dera Ismail Khan (Khyber Pakhtunkhwa, Pakistan), represents a vulnerable rural setting where drinking water quality and sanitation conditions may contribute significantly to disease transmission. This study aimed to determine the prevalence of zoonotic parasites in different drinking water sources and to evaluate household water accessibility and sanitation practices in the study area. A cross-sectional study was conducted in six rural union councils comprising 24 villages and 600 households, and a total of 450 water samples were collected from ponds, tube wells, and drainage sources. Samples were processed using filtration and centrifugation techniques. Parasitic organisms were identified through modified Ziehl–Neelsen staining for acid-fast parasites (Cryptosporidium spp., Toxoplasma gondii) and Lugol’s iodine wet mount for non–acid-fast parasites (Entamoeba histolytica, Giardia lamblia, Balantidium coli, and Fasciola hepatica). Statistical analysis was performed using SPSS, and differences in prevalence were analyzed using the Chi-square test at a significance level of p < 0.05. Tube wells were identified as the predominant source of drinking water, while flush toilets were the most commonly reported sanitation facility. Drainage water exhibited the highest prevalence of parasitic contamination, particularly Entamoeba histolytica, Cryptosporidium, and Giardia (p < 0.01), followed by pond water. In contrast, tube well water showed comparatively lower levels of contamination, although some samples tested positive for Giardia and Entamoeba histolytica. Household water accessibility varied significantly, with most families spending approximately 15 minutes to collect drinking water. Surface and drainage water sources pose substantial zoonotic and public health risks in the study area. Immediate interventions including improved water treatment systems, enhanced sanitation infrastructure, and community-based hygiene education are essential to reduce waterborne parasitic infections and improve public health outcomes in rural communities.
Keywords: Prevalence; Zoonotic Parasites; Drinking Water; Sanitation Practices; Dera Ismail Khan